STRENGTHENING BILATERAL RELATIONS THROUGH ARTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 6 April 2017 The 'Two Series of Artworks from Thailand' is the result of a collaboration between the Faculty of Fine Arts, Songkhla Rajabhat University; Schools of the Arts, Universiti Sains Malaysia (USM) and Muzium & Galeri Tuanku Fauziah (MGTF) USM, showcasing the fine artworks and assisting in the exchange of cultures between the two universities.